1994
DOI: 10.1080/00140139408964901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two types of chairs on stature change and comfort for individuals with healthy and herniated discs

Abstract: The objective of this study was to determine if stature change and perceived comfort are significantly different for individuals with either healthy or herniated discs when seated in a conventional chair or a sit-stand chair. Sixteen subjects were studied (5 young/healthy, 6 old/healthy, 5 old/herniated). Subjects performed a search task on a computer screen during two 2 h sessions for two consecutive days, with a different chair each day. Changes in stature were measured with a stadiometer. General comfort an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Previous research indicates that while infrequent in-chair movements over prolonged time duration could be considered a primary risk factor in the development of work related musculoskeletal disorders (Bhatnager et al, 1985), frequent movement could imply discomfort (Fenety and Walker, 2002). Other studies suggest that large changes in postures can be good indicators for discomfort (Vergara and Page, 2000; while the frequency and/or magnitude of the small movements are influenced by seating duration and level of discomfort (Fenety et al, 2000;Telfer et al, 2009;Jensen and Bendix, 1992;Michel and Helander, 1994). Some researchers have also evaluated the inchair movement from a "settling down time (SDT)" following initial contact with different seating surface and reported that testing for SDTs may be useful in the indirect objective assessment of wheelchair cushions .…”
Section: Introductionmentioning
confidence: 96%
“…Previous research indicates that while infrequent in-chair movements over prolonged time duration could be considered a primary risk factor in the development of work related musculoskeletal disorders (Bhatnager et al, 1985), frequent movement could imply discomfort (Fenety and Walker, 2002). Other studies suggest that large changes in postures can be good indicators for discomfort (Vergara and Page, 2000; while the frequency and/or magnitude of the small movements are influenced by seating duration and level of discomfort (Fenety et al, 2000;Telfer et al, 2009;Jensen and Bendix, 1992;Michel and Helander, 1994). Some researchers have also evaluated the inchair movement from a "settling down time (SDT)" following initial contact with different seating surface and reported that testing for SDTs may be useful in the indirect objective assessment of wheelchair cushions .…”
Section: Introductionmentioning
confidence: 96%
“…In their comparison between two seats it was found that the seat with the lowest stature shrinkage an lowest spinal force was always the seat with the least discomfort. Similarly, a tendency towards less general discomfort at less stature loss was found by Michel and Helander (1994), but only in a specific subgroup of their subjects: 30 -44 year old people with herniated discs. From the study of van Diee¨n et al (2001) no relationship could be established as their conditions concerning dynamic and fixed seats were only discriminative for spinal shrinkage and not for local discomfort.…”
Section: Spinal Loadmentioning
confidence: 99%
“…One study (Gadge & Innes, 2007) reported less LBD and OBD among pain-free participants when using a saddle chair with a backrest, but this was offset by an increase in buttock discomfort. Another study reported reduced LBD when sitting in less hip flexion among people with LBP (Michel & Helander, 1994), however pain-free participants reported greater discomfort using this chair. Finally, some limited evidence to support the use of reducing seated hip flexion was observed in two studies that reported a reduction in the activation of some paraspinal muscles (van der Heide et al, 2003) and enhanced subjective acceptability compared to a freely tiltable chair .…”
Section: Sitting Discomfortmentioning
confidence: 99%